PERFECTIONISM AND AFFECT AS DETERMINANTS OF SELF-PERCEIVED MOTOR COMPETENCE IN PRIMARY SCHOOL CHILDREN (Kinesiology, 2022)
The aim of this study was to analyze the primary school students’ perception of their motor competence in the area of Physical Education, with respect to the affective domain and improvement. The sample consisted of 428 primary school students aged between 8 and 12 years (M=10.43; SD=0.837) (Castilla La Mancha, Spain). Perceived motor competence (PMC) was measured by the Perception of Competence Questionnaire (POC); perfectionism was measured by the three subscales of the Child Perfectionism Questionnaire, and, finally, affectivity was assessed by the PANAS (Positive and Negative Affect Schedule) questionnaire. Positive correlations were obtained between all the dimensions of the PMC and self-improvement (p